A comparative study of cord blood haemoglobin and ferritin in normotensive versus preeclamptic patients - Ratna Kanta Talukdar; Sasindra Kumar Das; Indira Dokania (Barpeta Obstetrics and Gynaecological Society, 2021)
Background: During pregnancy, newborn development is directly affected by mother's well being. In India pregnancy induced hypertension incidence corresponds to be around 15%. The babies born to hypertensive mother have higher incidence of haematological changes. Due to uteroplacental vascular insufficiency or due to chronic foetal hypoxia there is increased iron utilization during enhanced erythropoiesis. Objectives: The aim is to compare the cord blood haemoglobin and ferritin level in newborns of normotensive versus preeclamptic patients. Materials and methods: It is a hospital based prospective case control study conducted from June 1st 2019 to 31st May 2020 for a period of one year. Over the study period, total 200 patients are included in the study and analysis of cord blood haemoglobin and ferritin level of 100 preeclamptic (case) and 100 normotensive (control) mothers were done. All data were analysed using SPSS version 21. A p - value <0.05 is considered as statistically significant at 5% level of significance. Results: Out of 100 preeclamptic patients 96% were booked cases and their mean age was 24.34±3.77 years and out of 100 normotensives patients 99% were booked and their mean age was 23.71±3.72 years. Haemoglobin level were found to be significantly higher in the preeclamptic group (case) as compared to normal group (control) with p value of <0.004 and mean value of 16.91 and 17.39 in control and cases respectively. In case of ferritin, the level were found to be significantly lower in the preeclamptic group as compared to normal group with p value <0.0001 and mean value of 158.94 and 76.98 in control and cases respectively. Conclusion: The chronic intrauterine hypoxia caused by preeclampsia causes significant changes in the haematological values in these babies.